Searching for the Past, Writing for the Present: Charles Ryle Fay and Newfoundland’s Contested Past - Ludlow, Peter (Acadiensis, 2010)
In the autumn of 1953 the Cambridge economic historian, C.R. Fay, presented a series of lectures at Memorial University based on his tours of the province. As a collector of all things Newfoundland and an observer of island’s shifting place within empire, Fay laid the foundation for a cultural renaissance in Newfoundland studies. Ultimately, however, the scope of his project, his personal bias, and indifference to the island’s historiography undermined his research and his significance as a historian of Newfoundland. Résumé À l’automne de 1953, C.R. Fay, historien de l’économie de Cambridge, a présenté une série d’exposés à la Memorial University inspirés de ses voyages dans la province. Collectionneur de tout ce qui était de Terre-Neuve et observateur de la place changeante de l’île au sein de l’empire, Fay a posé les fondements d’une renaissance culturelle en études terre-neuviennes. Cependant, ses recherches et son importance en tant que spécialiste de l’histoire de Terre-Neuve ont été minées, en fin de compte, par l’étendue de son projet, son parti pris personnel et son indifférence envers l’historiographie de l’île.